2011
DOI: 10.1016/j.ijantimicag.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Potent antiviral activity of brequinar against the emerging Cantagalo virus in cell culture

Abstract: In the present work, the antiviral activity of brequinar (BQR) against the replication of Cantagalo virus was evaluated. BQR is a potent inhibitor of cellular dihydroorotate dehydrogenase, an enzyme of the de novo pyrimidine biosynthetic pathway. Infection in the presence of 0.5μM BQR reduced virus progeny production by >90%, revealing an EC(50) (drug concentration required to inhibit 50% of virus replication) of 0.017μM. Replication of other orthopoxviruses was also inhibited by BQR at similar levels. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
(66 reference statements)
2
11
0
Order By: Relevance
“…Immunosuppression during certain infections such as those caused by vaccinia results in exacerbation of disease [40,41]. To avoid this problem, Schnellrath and Damasco [42] suggested that brequinar, a pyrimidine pathway inhibitor, might be used topically against cutaneous vaccinia infections.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppression during certain infections such as those caused by vaccinia results in exacerbation of disease [40,41]. To avoid this problem, Schnellrath and Damasco [42] suggested that brequinar, a pyrimidine pathway inhibitor, might be used topically against cutaneous vaccinia infections.…”
Section: Discussionmentioning
confidence: 99%
“…Virus infection analysis was performed by plaque reduction assay as described previously [ 22 ] with some modifications. Briefly, a total of RD cells (3 × 10 5 ) were seeded into six-well plates and cultured until 80% confluency.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the anti-EV71 activity of the baicalin, the experiments were performed according to the previously described method [ 22 ]. Baicalin was diluted in serum-free DMEM to 0, 6.25, 12.5, 25, and 50 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Group E included Brequinar, a known inhibitor of dihydroorotate dehydrogenase (DHODH). Brequinar has been described to have broad-spectrum antiviral activity against a large number of viruses ( Table 7 ) [ 52 , 53 , 54 , 55 , 56 , 57 ]. Brequinar has also been shown to have anti-ZIKV activity in Vero cells infected with ZIKV MR-766 and PRVABC59 (EC 50 of 0.08 and 0.08 µM, respectively), and in Vero cells infected with ZIKV MR-766 in pre-treatment conditions (EC 50 of 0.3 µM) [ 34 , 56 ].…”
Section: Discussionmentioning
confidence: 99%